Aerodynamic Performance Optimization on NACA 2412 Airfoil Flap With The Addition of Riblets - Faadihillah, Almer; Hariyadi Suranto Putro, Setyo; Wulansari, Ajeng (SAINSTECH NUSANTARA, 2025)
The development of technology in the world of aerodynamics, one of which is research on airfoils. There have been many various studies that have been used to examine airfoils in various flap configurations according to their use. along with the development of the times, research is increasingly easy to do without taking up a lot of time and spending a lot of money. Aerodynamic characteristics are very important in the field of aerodynamic application science aimed at obtaining the maximum performance of an airfoil shape. Therefore, in this case, research on the aerodynamic characteristics of an airfoil is very necessary to get results in the form of airfoil configuration development with force output results for better performance. The results of this study indicate that there is an increase in the performance of NACA 2412 airfoil with the addition of v-groove riblets compared to without v-groove riblets. The existence of v-groove riblets, can delay the occurrence of separation. The simulation shows that the highest lift coefficient increase occurs at α = 14˚ with an increase of 3% lift coefficient and can reduce drag by 7.3% at α = 2˚ so it can be concluded by adding riblets to the airfoil can improve the performance of the Airfoil